MENINGKATKAN KEPUTUSAN PEMBELIAN KONSUMEN PADA TOKO QUEEN BIKERS SHOP PADANG MELALUI KELENGKAPAN PRODUK DAN KUALITAS PELAYANAN - Egim, Ash Shadiq; Fermayani, Riche; Yuliana, Liza; Dirgantara, Muhammad Bayu (Bisnis-Net, 2024)
This research was conducted to determine the effect of Product Completeness and Service Quality on Consumer Purchase Decisions at Queen Bikers Shop in Padang City. The analysis technique used in this study is quantitative with multiple linear regression analysis. This study used 97 respondents as a research sample by conducting a survey of consumers at the Queen Bikers Shop shop. The results of the study prove that the two variables, namely Product Completeness and Service Quality, have a positive and significant effect on Purchasing Decisions at the Queen Bikers Shop.Keywords: Product Completeness, Service Quality, and Purchasing Decisions